STUDY OF WATER POTENCY FOR DRINKING WATER SYSTEM DEVELOPMENT IN SUNGAI PENUH, BANGKO DAN SAROLANGUN CITY AT BATANG TEMBESI SUB WATERSHED JAMBI PROV. EQUATORIAL CLIMATE ZONE - ILFAN, FREDDY
Rainfall and river flow data are used to examine potential changes in water resources in Batang Tembesi Sub-watershed which is the largest sub-watershed of the Batang Hari river basin in the Province of Jambi. Rainfall trend in 9 (nine) rainfall stations and river flow in 8 (eight) discharge stations were determined to see the annual baseflow, runoff coefficient, and the tendency of the average changes. Multiple linear regression 4 (four) variables are used to fill in the blanks, either in the rain or discharge station. Statistical hydrologic model was used to determine baseflow and annual runoff coefficients, while the normal frequency distribution, lognormal and log Pearson III, with nonparametric tests using chi-square and Kolmogorov-Smirnov were used to determine dry and wet discharge. 5-year moving average is used to minimize the randomness of rain and discharge so the trend can be observed. Rainfall occurs in almost all of rain station tends to decrease, except for the rain that was located in the western of sub-watershed. This occurs because the affected wavy morphology conditions and high elevation. Changes in land use also affect the average discharge and rainfall. In terms of the reliability of raw water for drinking water system, the quantity is abundant. However, heavy rainfall in equatorial zone will cause a destructive force that is higher than that on the island of Java which has a pattern of monsoon rainfall.